Impact of Antiretroviral Regimens on Cerebrospinal Fluid Viral Escape in a Prospective Multicohort Study of Antiretroviral Therapy-Experienced Human Immunodeficiency Virus-1–Infected Adults in the United States. (3rd April 2018) - Mukerji, Shibani S; Misra, Vikas; Lorenz, David R; Uno, Hajime; Morgello, Susan; Franklin, Donald; Ellis, Ronald J; Letendre, Scott; Gabuzda, Dana
Abstract : Protease inhibitors were independent predictors of cerebrospinal fluid (CSF) escape in antiretroviral therapy (ART)–experienced human immunodeficiency virus–infected adults. M184V/I combined with thymidine analog mutations were more frequent in adults with CSF escape compared to no escape. These findings suggest optimizing ART may reduce likelihood of CSF escape. Abstract: Background: Cerebrospinal fluid (CSF) viral escape occurs in 4%–20% of human immunodeficiency virus (HIV)–infected adults, yet the impact of antiretroviral therapy (ART) on CSF escape is unclear. Methods: A prospective study of 1063 participants with baseline plasma viral load (VL) ≤400 copies/mL between 2005 and 2016. The odds ratio (OR) for ART regimens (protease inhibitor with nucleoside reverse transcriptase inhibitor [PI + NRTI] vs other ART) and CSF escape was estimated using mixed-effects models. Results: Baseline mean age was 46 years, median plasma VL, and CD4 count were 50 copies/mL, and 424 cells/μL, respectively. During median follow-up of 4.4 years, CSF escape occurred in 77 participants (7.2%). PI + NRTI use was an independent predictor of CSF escape (OR, 3.1; 95% confidence interval, 1.8–5.0) in adjusted analyses and models restricted to plasma VL ≤50 copies/mL ( P < .001). Regimens that contained atazanavir (ATV) were a stronger predictor of CSF viral escape than non-ATV PI + NRTI regimens. Plasma and CSF M184V/I combined with thymidine-analog mutations were more frequent in CSF escape vs no escape (23% vs 2.3%). Genotypic susceptibility score–adjusted central nervous system (CNS) penetration-effectiveness (CPE) values were calculated for CSF escape with M184V/I mutations (n = 34). Adjusted CPE values were low (<5) for CSF in 27 (79%), indicating suboptimal CNS drug availability. Conclusions: PI + NRTI regimens are independent predictors of CSF escape in HIV-infected adults. Reduced CNS ART bioavailability may predispose to CSF escape in patients with M184V/I mutations.